Unlocking the power of the wind: Innovations in smart hybrid vertical axis wind turbines - Irawan, Elysa Nensy; Shibuya, Kai; Yamashita, Ken-Ichiro; Fujita, Goro (International Journal of Renewable Energy Development, 2024)
As global concerns about CO2 emissions grow, the development of green energy sources like wind power has become increasingly important. Two significant strengths of vertical-axis wind turbines relative to horizontal-axis models are their capacity to initiate rotation under minimal wind conditions and their versatility to operate effectively regardless of wind direction. This paper explores the innovation of smart hybrid vertical axis wind turbines, which combine drag and lift principles for enhanced performance with a focus on rotor switching mechanisms to optimize performance across varying wind conditions. The methodology involves experimental investigations using a small hybrid Savonius-Darrieus model, with 14cm height and 10cm diameter. The data indicates that the optimal rotor switching occurs at a tip speed ratio of 1.7. The turbine is designed to operate in hybrid mode at tip speed ratios below 1.7 and switch to single Darrieus mode at higher tip speed ratios. Performance evaluation metrics include tip speed ratio, moment coefficient, and power coefficient. Results indicate that the smart hybrid model exhibits superior performance compared to traditional hybrid and single Darrieus configurations. Through empirical studies and computational analysis, the Smart Hybrid model shows significant enhancements, with a 175% increase in initial torque compared to single Darrieus model and a 12.12% improvement in maximum power coefficient compared to traditional hybrid configurations.